Community psychology in Zimbabwe: past, present and future - Chireshe, Regis; Kasayira, Joseph M.; Mudhovozi, Pilot; Mapfumo, John; Gwandure, Kelvin (National Inquiry Services Centre, 2021)
The study describes and evaluates community psychology in Zimbabwe. We distinguish between a professional with the title ‘community psychologist’ and the practice of the field of community psychology in Zimbabwe. Community psychology services in Zimbabwe include the provision of education to all school- going age children, and free health services and housing for all. We also consider community psychology applications in the context of the HIV and AIDS pandemic, rising unemployment, homelessness, child abuse, disabilities, disasters and other hardships from urbanization, economics, and other challenges. Psychologists and other professionals offer community psychology services in the context of these challenges.